New, hybrid and fractured: cinema contemporary narratives - Cadenas, Alexis (situArte, 2023)
Truly contemporary films are new, hybrid, fractured narratives that are, also, necessarily original and strange. In this essay we will just present the challenges and opportunities that lie ahead, such as the new technological platforms, the strange storytelling that is occurring on these new platforms, and the swapping of roles between auteurs and audiences, but we need to start (continue) this conversation if we want cinema to survive, or die for something different to emerge.After briefly discussing what contemporary cinema is or can be, and exploring some examples of the new, hybrid and fractured narratives thatare emerging, we will end our account with a reflection on originality and where it can be found in the process of creating these new pieces.